Utilization of Digital Tutorials in Improving Motivation to learn And Students' Understanding of Islamic Education Subjects In Junior High School Negeri 1 Peureulak - Elmayanti, Elmayanti; Amiruddin, Amiruddin; Sabaruddin, Sabaruddin (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study objective is to evaluate the utilization of digital tutorials in Islamic Religious Education instruction, assess their influence on students' learning motivation, and investigate their role in enhancing students' comprehension of IRE content at Junior High School Negeri 1 Peureulak. A qualitative descriptive methodology was utilized, with data gathered via observations, interviews, and documentation. The results show that adding digital tutorials is a change in teaching style that leads to more humanistic, contextual, and technology-based learning. Digital tutorials have been shown to improve students' motivation, understanding, and religious character through careful preparation, thoughtful implementation, and ongoing evaluation. Digital tutorials greatly boost students' enthusiasm, activity, creativity, and independence in learning. This is because digital media combine visual, audio, and interactive elements that make learning more interesting and meaningful, which encourages both intrinsic and extrinsic motivation. Strong school support, access to digital resources, competent teachers, cooperation between teachers and IT personnel, and high student interest are all aspects that help. But there are still certain problems, such as a lack of infrastructure, limited time for learning, teachers' variable levels of computer proficiency, and students not having equal access to digital gadgets.